IMPLEMENTATION OF HYGIENIC FISH MARKET MODEL AND ITS IMPLICATION ON MARKET STRUCTURE AND MARKETING EFFICIENCY OF SEA FISH IN JEMBER REGENCY - Syamsul Hadi; Edi Sutiarso; Arief Awaluddin; Toni Herlambang (UPT Penerbitan Universitas Jember, 2017)
The increasing trend of fishery business development in Jember Regency, in fact notaccompanied by a decent Fishermen's (proportional) Exchange Rate. This is due to thelimited fishermen to access market opportunities, technology, and easy capital, so that thefishermen have not enjoyed much real results. This condition is caused by the production ofthe catch is still low, the quality of the fish has not met the standard, the price of fish is lowand the lack of support from the business world as well as the prerequisite condition of thefish market facilities and infrastructure are clean, so less attract consumers to come buy. Thepurpose of this research is to analyze the impact of the implementation of marketing strategymodel of marine fish marketing through hygienic fish market to new market structure,marketing channel pattern, and marketing efficiency of marine fish in Jember Regency. Inorder to achieve the purpose of this research, it is used descriptive quantitative andqualitative research methods through survey technique of acidental sampling andsnowbolling sampling. Types of population in this study are Fishermen, Traders includinggroups who are members of Poklaksar, and Consumers. The data collection techniques usedFGD, Indepth Interview and observation. Data analysis used included descriptive analysis,and marketing margin. The results of the research conclude: 1) Market structure in HygienicFish Market model in Jember Regency is classified as Monopolistic Market which is moreaimed at oligopoly market, 2) Pattern of marine fish marketing channel that occur in hygienicfish market model is covering three kinds of marketing channel pattern, and 3) Hygienic FishMarket Model can provide a fairly high share of Fisher (Farmer's share) margin (58.95%),meaning that the marketing of marine fish model has been achieved Efficiency.